Workspace and pivot point for robot‐assisted endoscope guidance in functional endonasal sinus surgery (FESS). Issue 1 (18th June 2014) - Eichhorn, Klaus Wolfgang; Westphal, Ralf; Last, Carsten; Rilk, Markus; Bootz, Friedrich; Wahl, Friedrich M.; Jakob, Mark
Abstract Background For the further development of robot‐assisted endoscope guidance in functional endoscopic sinus surgery (FESS), ground data about the workspaces and endoscope movements in conventional FESS are needed. Methods Applying a self‐developed marker‐based tracking system, we collected the pose data (position and orientation) of the endoscope and all other instruments used in five real sinus surgeries. Results The automated segmentation of the endoscope poses shows the shape of a hourglass, with a pivot region or pivot point at the 'waistline' of the hourglass, close to the nasal entrance in the nasal dome. Conclusion We were able to identify a pivot point at the waistline of the segmented endoscope poses. The size of the pivot point corresponds with the diameter of the 4 mm endoscope. Because of the reduction to four degrees of freedom for endoscope motions (three rotations and one translation), easier and safer robot‐assisted endoscope guidance becomes feasible. Copyright © 2014 John Wiley & Sons, Ltd.